Why Health Knowledge Does Not Translate into Health Behavior: Educational and Psychological Perspectives - Wicher, Anna; Radziwon, Maja; Borowski, Konrad; Pastuszek, Oskar; Bolesta-Okuniewska, Emilia; Michalak, Paweł; Marchwińska-Pancer, Aleksandra; Kopeć, Katarzyna; Ceryn, Julia (Journal of Education, Health and Sport, 2026)
Despite the widespread availability of health-related information, adherence to health-promoting behaviors remains insufficient in many populations worldwide [1,2]. Research indicates that increasing health knowledge alone does not reliably lead to sustained lifestyle change, suggesting the presence of additional educational, psychological, and contextual determinants shaping health behavior [5,8,16]. The aim of this narrative review is to analyze why health knowledge frequently fails to translate into health-promoting action, with particular emphasis on educational and psychological perspectives [5,7]. Peer-reviewed literature indexed in PubMed and Scopus and publications issued by the World Health Organization were considered [1–3,10]. The reviewed evidence suggests that limited health literacy, low self-efficacy, motivational and emotional factors, habitual behavior patterns, and environmental constraints substantially moderate the relationship between knowledge and action [6,9,18–21,24–28]. These determinants are summarized in Table 1 and indicate that effective health education should move beyond information transfer and incorporate behavioral competencies, psychological support, and context-sensitive approaches to promote sustainable health behavior change [3,5,7,26–28].